BASIC CONCEPTS OF FACIAL BONE DEFECTS AND MODERN APPROACHES TO THEIR RECONSTRUCTION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Facial bone defects are a complex and pressing problem in the medical field. These defects are often the result of trauma, surgery, congenital defects, or illnesses. Facial bone defects not only negatively affect appearance, but can also damage vital functions such as breathing, digestion, and speech. For this reason, effective restoration of facial bone defects is of great importance in medicine and plays an important role in improving the quality of life of patients.